2022
DOI: 10.1038/s41598-022-08589-z
|View full text |Cite
|
Sign up to set email alerts
|

Dome-arrayed chitosan/PVA hydrogel-based solar evaporator for steam generation

Abstract: Water evaporation systems with solar energy as the primary driving energy have received extensive attention in recent years. This work studies the preparation method and performance of hydrogel evaporators using chitosan and polyvinyl alcohol (PVA) as a framework and carbon nanoparticles (CNPs) as the photothermal material. The evaporation rate of CPC (chitosan/PVA and CNPs) hydrogel obtained reaches 2.28 kg m−2 h−1. Simultaneously, a three-dimensional structure is designed based on the two-dimensional double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Based on the thickness of the solar evaporator, they may be divided into two categories: 2D structures and 3D structures. The 2D structures are normally made of various membranes [145][146][147][148], papers [127,149,150], and fabrics [151][152][153], while the 3d structures are constructed using different types of foams [154,155], hydrogel or aerogel [156,157], bio-derived materials (i.e., wood) [158], ceramic fiber wool and stainless-steel mesh [149], etc. However, the structures of the solar evaporators are not limited to their thickness.…”
Section: Structure Of Solar Evaporatorsmentioning
confidence: 99%
“…Based on the thickness of the solar evaporator, they may be divided into two categories: 2D structures and 3D structures. The 2D structures are normally made of various membranes [145][146][147][148], papers [127,149,150], and fabrics [151][152][153], while the 3d structures are constructed using different types of foams [154,155], hydrogel or aerogel [156,157], bio-derived materials (i.e., wood) [158], ceramic fiber wool and stainless-steel mesh [149], etc. However, the structures of the solar evaporators are not limited to their thickness.…”
Section: Structure Of Solar Evaporatorsmentioning
confidence: 99%
“…Developed via in-situ synthesis, this material effectively localizes heat and maintains high performance and stability. Zhu et al 19 prepared chitosan/polyvinyl alcohol and carbon nanoparticles double layer hydrogel, achieving excellent evaporation rate of 2.28 kg/m² h. Zhou et al 20 demonstrated a solar evaporator utilizing hydrophilic polymer and reduced graphene oxide hydrogel, capable of producing vapor at a high rate of 2.5 kg/m² h under one sun irradiation. Because of the reduced vaporization enthalpy within the CNTs/starch hybrid biohydrogel, Xu et al 21 developed a composite Janus-carbon nanotube/polyvinyl alcohol hydrogel and achieved a high evaporation rate of 2.77 kg/m²h, with an efficiency of approximately 88% under 1.0 sun irradiation.…”
Section: Articlementioning
confidence: 99%
“…Developed via in situ synthesis, this material effectively localizes heat and maintains high performance and stability. Zhu et al 19 prepared chitosan/polyvinyl alcohol and carbon nanoparticle double layer hydrogels, achieving an excellent evaporation rate of 2.28 kg m −2 h −1 . Zhou et al 20 demonstrated a solar evaporator utilizing a hydrophilic polymer and a reduced graphene oxide hydrogel, capable of producing vapor at a high rate of 2.5 kg m −2 h −1 under one sun irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrogels are synthesized through physical cross-linking methods, such as freeze-thaw cycles, or chemical cross-linking to form stable three-dimensional network structures. In OA treatment, PVA hydrogels are predominantly utilized as artificial substitutes or repair materials for joint cartilage, providing effective cushioning and shock absorption that mitigate joint inflammation and pain [69]. However, PVA hydrogels exhibit relatively low bioactivity, and their mechanical strength and durability may be insufficient for long-term joint pressure and wear, particularly in knee applications.…”
Section: Polyvinyl Alcoholmentioning
confidence: 99%